1994
DOI: 10.1111/j.1474-919x.1994.tb01086.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of food abundance on breeding performance and adult time budgets of Guillemots Uria aalge

Abstract: The breeding performance, food fed to chicks and adult time budgets of Guillemots Urin aalge were examined in a year of high and a year of low food availabiIity. There was no difference between the 2 years in reproductive success, although the rate of chick feeding, chick weight and fledging success were greater in the year of high food availability. On average, chick prey items were larger in the poor food year, but this was i n s u~~i e n t to compensate €or the lower feeding frequency. Chick feeding frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…Seabirds typically adjust activity budgets with respect to prey availability (Burger & Piatt 1990, Uttley et al 1994, Zador & Piatt 1999, and the present study provides evidence that marbled murrelets do so as well. Murrelets foraged most intensively early in the 2005 season when prey was least abundant and more dispersed.…”
Section: Threshold and Timing Effects Of Preysupporting
confidence: 66%
See 2 more Smart Citations
“…Seabirds typically adjust activity budgets with respect to prey availability (Burger & Piatt 1990, Uttley et al 1994, Zador & Piatt 1999, and the present study provides evidence that marbled murrelets do so as well. Murrelets foraged most intensively early in the 2005 season when prey was least abundant and more dispersed.…”
Section: Threshold and Timing Effects Of Preysupporting
confidence: 66%
“…Flexibility in foraging behaviour has been demonstrated widely in seabirds, and in particular piscivorous alcids (Alcidae), that adjust their activity budgets, spending more time foraging in years when foraging conditions are poor (Burger & Piatt 1990, Uttley et al 1994, Litzow & Piatt 2003. Behavioural responses to prey may be observed much earlier than physiological or reproductive responses ), yet despite the apparent flexibility of activity budgets for many seabirds, thresholds may exist whereby foraging flexibility can no longer buffer reproductive success against very low food availability (Dall & Boyd 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This last result indicates that the food availability around SG may be scarce, which agrees with previous studies that reported lower feeding frequencies (Granadeiro et al 1998b) and longer foraging trips at this colony (Catry et al 2009;Paiva et al 2010b), when compared to BE. Indeed, the length of foraging trips is known to be largely influenced by the local food availability (Uttley et al 1994) and by the distance to the most profitable areas (Paiva et al 2010c). Moreover, as the number of breeding shearwaters at SG is much larger than at BE (Granadeiro et al 2006;Lecoq et al 2011), intraspecific competition could also lead to differences in the foraging strategies between colonies (Lewis et al 2001;Grémillet et al 2004).…”
Section: Foraging Strategy and Chick Conditionmentioning
confidence: 99%
“…Thus our predictions were met because prey were more abundant in urban habitats as expected (Blair 1996;Tratalos et al 2007), and it is well known that food abundance is typically the major driver of breeding performance among birds in particular (e.g. Martin 1987;Uttley et al 1994;Perrig et al 2014;Pollock et al 2017) and animals in general (e.g. Korpimäki et al 1991;Wauter and Lens 1995;Heesen et al 2013) Our results agree with another more detailed study based on a single urban raptor population in South Africa, which concluded that the stability of prey in urban environments is sufficient to maintain healthy offspring of another top avian predator (Suri et al 2017).…”
Section: Discussionmentioning
confidence: 85%